Universal Restrictions in Reading: What Do French Beginning Readers (Mis)perceive? - Maïonchi-Pino, Norbert; Carmona, Audrey; Tossonian, Méghane; Lucas, Ophélie; Loiseau, Virginie; Ferrand, Ludovic (Frontiers in Psychology, 2020)
Despite the many reports that consider statistical distribution to be vitally important in visual identification tasks in children, some recent studies suggest that children do not always rely on statistical properties to help them locate syllable boundaries. Indeed, sonority – a universal phonological element – might be a reliable source for syllable segmentation. More specifically, are children sensitive to a universal phonological sonority-based markedness continuum within the syllable boundaries for segmentation (e.g., from marked, illegal intervocalic clusters, ‘jr’, to unmarked, legal intervocalic clusters, ‘rj’), and how does this sensitivity progress with reading acquisition? To answer these questions, we used the classical illusory conjunction paradigm. Forty-eight French typically developing children were tested in April (T1), October (T2) and April (T3; 20 children labeled as “good” readers, M chronological age at T1 = 81.5 ± 4.0; 20 children labeled as “poor” readers, M chronological age at T1 = 80.9 ± 3.4). In this short-term longitudinal study, not only we confirmed that syllable segmentation abilities develop with reading experience and level but the Condition × Sonority interaction revealed for the first time that syllable segmentation in reading may be modulated by phonological sonority-based markedness in the absence or quasi-absence of statistical information, in particular within syllable boundaries; this sensitivity is present at an early age and does not depend on reading level and sonority-unrelated features.